THE POLITICAL DEVELOPMENT OF ISLAMIC CONSTITUTIONAL IN INDONESIA - Ma'adul Yaqien Makkarateng (Jurnal Al-Dustur, 2019)
The development of Islamic state administration politics in Indonesia from time to time starting from the Dutch occupation, the Japanese occupation, independence, the old order, the new order, and Islamic politics during the reformation period experienced different shocks, not only in the form of structural reforms. Government but to the grassroots of society. Then over time, the Ulama realized that their struggle would not succeed if they continued in traditional ways. Therefore, it is necessary to make changes which, although originating from the colonial influence itself, are struggling through organizations, both in the field of social education or in the field of political administration. The presence of Ulama in the political field should have a positive impact, in the sense of contributing to the creation of a moral, political structure, because the Ulama is a moral symbol. However, when Ulama have been polarized in such a way, so often between one Ulama and other Ulamas face each other and defend their respective parties. This condition will cause divisions, and the effect is to confuse the people so that it will weaken the power of the Muslims themselves, which in turn is often used by other party groups.